Talking to Children and Families about Chronic Pain: The Importance of Pain Education—An Introduction for Pediatricians and Other Health Care Providers - Helen Koechlin; Cosima Locher; Alice Prchal (Children, 2020)
Chronic pain in children and adolescents is a common and debilitating health problem. This narrative review will give a brief overview on what pediatric chronic pain is and what treatment options there are for children and adolescents. The specific emphasis will be on pediatric chronic pain education and communication: this narrative review aims to show how important a good patient–health care provider relationship is—it builds the foundation for successful communication—and how this relationship can be established. In addition, we will present five steps that health care providers can perform to explain pediatric chronic pain to patients and their parents and what to keep in mind in their clinical routine. Our review is intended for pediatricians and other health care providers who treat pediatric patients with chronic pain but might feel uncertain on how to best communicate with them.